ln(x+1)+ln(x)-ln(2)=0

Simple and best practice solution for ln(x+1)+ln(x)-ln(2)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ln(x+1)+ln(x)-ln(2)=0 equation:


Simplifying
ln(x + 1) + ln(x) + -1ln(2) = 0

Reorder the terms:
ln(1 + x) + ln(x) + -1ln(2) = 0
(1 * ln + x * ln) + ln(x) + -1ln(2) = 0
(1ln + lnx) + ln(x) + -1ln(2) = 0

Multiply ln * x
1ln + lnx + lnx + -1ln(2) = 0

Reorder the terms for easier multiplication:
1ln + lnx + lnx + -1 * 2ln = 0

Multiply -1 * 2
1ln + lnx + lnx + -2ln = 0

Reorder the terms:
1ln + -2ln + lnx + lnx = 0

Combine like terms: 1ln + -2ln = -1ln
-1ln + lnx + lnx = 0

Combine like terms: lnx + lnx = 2lnx
-1ln + 2lnx = 0

Solving
-1ln + 2lnx = 0

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'ln'.
ln(-1 + 2x) = 0

Subproblem 1

Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-1 + 2x)' equal to zero and attempt to solve: Simplifying -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing l to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Add '-2x' to each side of the equation. 2x + -2x = 1 + -2x Combine like terms: 2x + -2x = 0 0 = 1 + -2x Simplifying 0 = 1 + -2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 6-6x=-6x+6 | | 10x-6=4+5x | | 24-x^2-12x=0 | | f(x)=10x^4+7x^3-27x^2+2x+8 | | x^2+3x-1=17 | | (4x+11)+(3x+1)=180 | | (x-2)(x-2)(1)=169 | | 21x=3/4 | | (x+10)+(3x+18)=180 | | -20(3x-68)=-80(9x-38) | | (2x-5)+(4x-13)=90 | | 3x+7z=2-2y | | 4a^2=25a+21 | | 7(a-6)+13=3(a-7) | | 4(x+5)-3=23-2x-6+6x | | 7a-7a=15 | | 7(-6)+3y=12 | | 240=2x^2+2x | | 33%+14%= | | 10(x+5)=3(4x+3) | | .25x-.05=.2x+.15 | | .1(x+74)=2(2-x) | | 2x^3+13s^2+20s+20=0 | | 4xy+7xy+12xy+14xy= | | 2a-7=3(a+1)+9a+1 | | 2x-1=3.2 | | 2h^2-32=0 | | -52-18=x | | x+sqrt(5x+19)=-1 | | -20+(-17)=x | | 5ln(3y+45)=5 | | 11n-n^2=0 |

Equations solver categories